JARIMAH TERHADAP KEHORMATAN SIMBOL SIMBOL NEGARA - Haq, Islamul (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: This paper examines jarimah (criminal act) against the honor of the symbols of the State in terms of the perspectives of Indonesian criminal law and Islamic criminal law. By using decryption analysis methods derived from sources relating to positive-law (punitive law) and Islamic criminal law. From the analysis it can be concluded that in positive law the formulation of the use of State symbols and sanctions for violators has been set forth firmly in the law of the State of Indonesia and the Criminal Code while in Islamic Criminal Law, although the crime against the honor of the symbols of the state is not explicitly discussed, but there are verses of the Qur'an and hadith prophets which prohibit the criminal act of contempt in general. Islam also has universal values that teach about the honor of the nation and the love of the homeland. This is contrary to the criminal act of contempt against the symbols of the state. Abstrak: Tulisan ini mengkaji mengenai jarimah (tindak pidana) terhadap kehormatan simbol-simbol Negara ditinjau dari persfektif hukum pidana Indonesia dan hukum pidana Islam. Dengan menggunakan metode analisis dekstriftif yang berasal dari sumber-sumber yang berhubungan dengan positive-law (hukum positif) dan hukum pidana Islam. Dari hasil analisis dapat disimpulkan bahwa dalam hukum positif rumusan penggunaan simbol-simbol Negara beserta sanksi bagi pelanggar telah diatur secara tegas di dalam undang undang Negara Indonesia dan KUHP sedangkan dalam Hukum Pidana Islam, meski tindak pidana terhadap kehormatan simbol-simbol negara tidak dibahas secara ekplisit, akan tetapi terdapat ayat-ayat al-Quran dan hadist nabi yang melarang tindak pidana penghinaan secara umum. Islam juga mempunyai nilai-nilai universal yang mengajarkan tentang kehormatan bangsa dan rasa cinta tanah air. Hal tersebut bertentangan dengan tindak pidana penghinaan terhadap simbol-simbol negara.